KEANEKARAGAMAN JENIS IKAN DAN KETERKAITANNYA PARAMETER FISIKA KIMIA PERAIRAN ESTUARI SUAKA MARGASATWA KARANG GADING KABUPATEN DELI SERDANG SUMATERA UTARA - Anggia Dolly Sibuea; Miswar Budi Mulya; Yunasfi Djayus (AQUACOASTMARINE, 2016)
The research species diversity of fish in estuary waters Karang Gading Wildlife Sanctuary was held in May-June, 2015. It was conducted in three stations by natural zones and utilization. This study aims to determine the diversity of fish species and strong influence parameters with the diversity of fish species in the estuary. The Fish densities were analyzed using the formula Odum (1994). The Diversity Index using the formula Ludwig and Reynolds (1988) and correlation with a diversity index of chemical physics parameters of waters using Pearson correlation analysis with a computerized method of SPSS version 18.00. The results of this study were 19 species of fish. The highest density at station 3 (18,401 ind / m2) and the lowest at station 2 (5,237 ind / m2). The highest diversity index at station 1 (2.35) and the lowest is station 3 (1.62). Current speed, pH, DO and BOD were very strong positively correlated to the value of fish diversity index while the temperature was very strong negative correlation to the index of fish diversity.Keywords : Fish, Diversity, Karang Gading Wildlife Sanctuary Estuary.